(3efGbH GdCSO GdZGdH eeRb GdcJGjH heXgQ GdYLGjHs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3fUQ Gddg Hf eMeO Hf eMeO Hf YHO GdcQje GdTjHGfqj, GdLRQj, CHh GdaJM, VjGA GdOjf, GdeYQha HGHf GdCKjQ GdcGJH,J (B637 (3g` s
(3ChdgG (B:s
(3hHYO agPg CMGOjK eSfOI eeG JhGJQ hUM hMSf ef CSfi efGbH GdEeGe GdZGdH eaQb GdcJGjH heXgQ GdYLGjH djK Hf ZGdH CejQ GdeDefjf CHj GdMSf Ydi Hf CHj WGdH s
(3BNQgG (B:s
(3CTgO HGddg hBjGJg TgGOI CQLh HgG YJbi Cf CHG HcQ hef HYOg KdGKI CFeI GdUOb GdeDefjf GdEeGe GdMSf Ydi Hf CHj WGdH Ydi jO eDdag eMeO Hf eMeO Hf GdLRQi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B98s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B1619) s
Keywords: (3GdMOjK h GdeUWdMs